Reviews of environmental contamination and toxicology. Volume 241 - Voogt, Pim de (Springer, 2016)
Reviews of Environmental Contamination and Toxicology attempts to provide concise, critical reviews of timely advances, philosophy and significant areas of accomplished or needed endeavor in the total field of xenobiotics, in any segment of the environment, as well as toxicological implications.
4 Rhizosphere, Rhizobacteria and Metal Transporters Used in Remediation Purposes.
Keywords: Pollution.; Environmental toxicology.; Toxicology.; elektronické knihy; electronic books